Drug interactions resulting from scheduling and errors in the preparation of antibacterials - Francisco Gilberto Fernandes Pereira; Geórgia Alcântara Alencar Melo; Nelson Miguel Galindo Neto; Rhanna Emanuela Fontenele Lima de Carvalho; Eugenié Desireé Rabelo Néri; Joselany Áfio Caetano (Universidade Federal do Ceará, 2018)
Objective: to identify drug interactions resulting from scheduling and errors in the preparation of antibacterials. Methods: observational and cross-sectional study carried out in medical clinics of a sentinel hospital. Data were collected through the observation of prescriptions and the preparation of 265 doses of antibacterials with the use of a check list. Results: the administration of Piperaciclina and Tazobactan prevailed, with 51 doses. The scheduling of antibacterials with another drug occurred predominantly in the morning. Interactions with injectable anticoagulants and between antimicrobials of different classes stood out. The scheduling was associated with the lack of availability of printed guidelines on medication administration (p=0.003). The main error was the dose (32.5%). Conclusion: the scheduling of antibacterials in the medical clinic may potentiate possible drug interactions and dose errors have been identified in the administration of drugs.